Safety Profile of Oral Anticoagulants in Elderly Atrial Fibrillation Patients: A Review Focused on Bleeding Risk in Secondary Stroke Prevention - Viviandhari, Daniek; Wiyati, Tuti (Brawijaya University, 2025)
The elderly population has the highest risks of bleeding due to oral anticoagulant use to prevent secondary stroke since causes higher levels of anticoagulant status fluctuation. However, the detailed information on safety issues regarding bleeding effect of oral anticoagulant from elderly population perspective with atrial fibrillation is still lacking. This narrative review was conducted to summarize the study findings from the present literature. This review was conducted using PubMed and Scopus database. Data were retrieved from 2017 until 2023. Articles were considered for inclusion if they discussed the safety of oral anticoagulant for secondary stroke prevention in Atrial Fibrillation (AF) patients. A total of 9 articles were extracted. The design of the studies, participant characteristics, and the risk of bleeding events were all assessed. The Hazard Ratio (HR) ranged from 2.82 to 0.58 across 5 trials. There were three occurrences of significant hemorrhage with delayed Non-Vitamin K Antagonist Oral Anticoagulants (NOACs) and seven cases with early NOACs. When comparing acute reperfusion to no reperfusion, the Odd Ratio (OR) of 1 study was 0.74. One study found that the incidence of significant bleeding was 2.1% in the case of standard warfarin use and 0% in the case of early apixaban use. Research comparing warfarin and rivaroxaban in patients with mild AF found a Relative Risk (RR) of 0.91. NOACs/Direct Oral Anticoagulants (DOACs) are relatively safe to use, while International Normalized Ratio (INR)-guided Vitamin K antagonists (VKAs) should be use with cautions in the elderly with AF for secondary stroke prevention concerning bleeding events, regardless of independence status (patient’s level of functional independence), presence of acute reperfusion treatment, Embolic Stroke of Undetermined Source (ESUS), Patent Foramen Ovale (PFO), and decreased renal function.